Chemo-rheological and morphology evolution of polymer modified bitumens under thermal oxidative and all-weather aging. (1st February 2021) - Sun, Guoqiang; Li, Bin; Sun, Daquan; Yu, Fan; Hu, Mingjun
Graphical abstract: Highlights: The leading role of polymer degradation and bitumen oxidation in various aging stages is different. All-weather aging imparts greater impacts to chemo-rheological properties of base bitumen and RPE bitumen than long-term aging. SBS bitumen is more affected by long-term aging compared with all-weather aging. SBS structures significantly mitigate the oxidation depth of SBS bitumen during all-weather aging. Mitigation effect of RPE bitumen on all-weather aging is weakened due to poor compatibility and dispersion. Abstract: In this paper, the styrene–butadienestyrene (SBS) modified bitumen, recycled polyethylene (RPE) modified bitumen and their base bitumen are aged by thermal oxidative aging and all-weather aging tests. The fluorescence microscopy (FM), thin layer chromatography, gel permeation chromatography, infrared spectroscopy and dynamic shear rheometer are used to trace the chemo-rheological and morphology evolution of various aged bitumens. FM observation and chemical investigation show that the leading role of polymer degradation and bitumen oxidation in various aging stages is different. SBS structures are mainly degraded at the short-term aging stage, while the oxidation of RPE bitumen in short-term aging process is more prominent than its polymer degradation due to its poor compatibility and dispersion. The bitumen oxidation becomes the leading process of long-term aging and all-weather aging for bitumens. Furthermore, the multi-scale analysis reveals that the all-weather aging imparts the far more pronounced impacts to the chemical and rheological properties of base bitumen and RPE bitumen than long-term aging, while SBS bitumen is more affected by long-term aging. Moreover, SBS bitumen has much more excellent aging resistance to the transitions of chemo-rheological properties than RPE bitumen and subsequent base bitumen. Especially, the deep effect of all-weather aging is analyzed by comparing the chemical variations of bitumens at different sampling depths. Results illustrate that the all-weather aging almost runs through the entire depth of base bitumen. In contrast, SBS spatial reticular structures can significantly mitigate the oxidation depth of SBS bitumen, whereas the mitigation effect of RPE bitumen on all-weather aging is weakened.